Autonomous AI: what does autonomy mean in relation to persons or machines? - Chia, H; Beck, D; Paterson, JM; Savulescu, J (Taylor & Francis, 2023)
Artificially intelligent machines are increasingly capable of accomplishing tasks that have until now been considered exclusively human abilities. One such task is the ability to invent. In 2021, an Australian court became the first court in the world to recognise an Artificially Intelligent system as the inventor in a patent application, raising the question of whether AI systems could be considered the responsible actor of their actions, instead of the human using the AI. This paper examines the question of autonomy: how the concept of autonomy underpins the granting of legal rights to humans, and whether it is justified to grant legal rights to AI systems that are autonomous. We propose that there are two distinct and separate concepts of autonomy, Person Autonomy and Machine Autonomy, and that this distinction can guide how the law should treat AI systems.